Robust PI/PID Controller Design for the Reliable Control of Plug Flow Reactor; Chemical Engineering Transactions; Vol. 43 - Mikhalevich S. S. Sergey Sergeevich; Rossi F. Francesco; Manenti F. Flavio; Baydali S. A. Sergey Anatolievich (2015, 2015)
Title screen